Concentration of dissolved organic carbon in the Baltic Sea, 1984-1985 - A K Yurkovskiy; S S Vladimirskiy (PANGAEA, 1989)
Dissolved organic carbon concentrations (DOC) were determined with a Photochem E3600 analyzer. Vertical distribution of DOC is discussed in terms of data from three stations for four seasons in 1984-1985. Concentration of particulate organic carbon (POC) was from 2.85 to 4.81 (6.84) mg/l, and its vertical profile was multipeaked, not always with a maximum at the surface. Vertical distribution of POC in basins of the Baltic Sea has a distinctive structure that varies with season and with hydrochemical conditions. It is largely governed by the metabolic cycle of organic matter, which is regulated in each layer by the hydrologic structure of water masses and by presence of zones that differ in nature of metabolism in communities.
Supplement to: Yurkovskiy, AK; Vladimirskiy, SS (1989): Structure of the vertical distribution of dissolved organic carbon in the Baltic Sea. Oceanology, 29(2), 168-172